2000
DOI: 10.1074/jbc.m000464200
|View full text |Cite|
|
Sign up to set email alerts
|

Thrombin-mediated Feedback Activation of Factor XI on the Activated Platelet Surface Is Preferred over Contact Activation by Factor XIIa or Factor XIa

Abstract: To study the pathways for initiation of intrinsic blood coagulation, activated human platelets were compared with dextran sulfate as surfaces for factor XI activation by factor XIIa, factor XIa, or thrombin. Activated gelfiltered platelets promoted the activation of factor XI (60 nM) by thrombin (0.02-10 nM, EC 50 ϳ100 pM, threshold concentration ϳ10 pM) at initial rates 2-to 3-fold greater than those obtained with dextran sulfate in the presence of either high molecular weight kininogen (45 nM) and ZnCl 2 (25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 36 publications
3
87
0
Order By: Relevance
“…Thus, FXI activation is required for normal hemostasis only in cases of significant hemostatic challenge, which is consistent with clinical observations that patients with congenital FXI deficiency generally have much milder bleeding than those with FVIII deficiency (hemophilia A) (15,16). Consistent with these observations is the demonstration that thrombin is more efficient than FXIIa or FXIa in activating FXI in vitro (13).…”
supporting
confidence: 76%
See 2 more Smart Citations
“…Thus, FXI activation is required for normal hemostasis only in cases of significant hemostatic challenge, which is consistent with clinical observations that patients with congenital FXI deficiency generally have much milder bleeding than those with FVIII deficiency (hemophilia A) (15,16). Consistent with these observations is the demonstration that thrombin is more efficient than FXIIa or FXIa in activating FXI in vitro (13).…”
supporting
confidence: 76%
“…For 10 mutants demonstrating diminished (Ͻ50% compared with WT thrombin) FXI activation, dose-response curves were constructed over a range of thrombin concentrations using the above protocol. Linear initial rates of FXIa generation with respect to time and enzyme (thrombin) concentration were observed in the presence of dextran sulfate as previously reported (8,9,13). EC 50 values were calculated using SigmaPlot software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have shed light on this conundrum. It has been shown that HK facilitates FXI binding to the surface of activated platelets, where it is rapidly activated to FXIa (18,20,43). Prothrombin may serve as a substitute for HK in this role, providing a plausible explanation as to why HK-deficient humans do not bleed (19).…”
Section: Resultsmentioning
confidence: 99%
“…Along similar lines, it has been shown that HK facilitates the binding of FXI to activated platelets (17,18). Once bound to the platelet surface, FXI is efficiently activated to FXIa by coagulation proteases such as thrombin and factor XIIa (FXIIa) (4,19,20).…”
Section: Coagulation Factor XI (Fxi)mentioning
confidence: 89%